Lumbar plexus formation of the Cebus apella monkey - Barros, Roseâmely Angélica de Carvalho; Prada, Irvênia Luiza de Santis; Silva, Zenon; Ribeiro, Adriana Rodrigues; Silva, Daniela Cristina de Oliveira (Brazilian Journal of Veterinary Research and Animal Science, 2003)
The non-human primates have been considered an important group among the diverse studied animals, having a great interest not only for the understanding of its own evolution, but also due to the fact that the detailed knowledge of its Anatomy can represent a relevant factor for its preservation and protection. In addition, concerning the neural system, the comparative study on the composition of the lumbo-sacral plexus representing the origin of the nerves that are destined to the pelvic members, shows a particular interest for being an anatomical segment involved in evolutionary aspects of posture and locomotion. The aim of this work was to study the origin, composition of the lumbar plexus in monkey Cebus apella in order to obtain a better comprehension of the Anatomy in this animal. Previous studies have not demonstrated any findings on the topic in this species. Twenty animals, 10 male and 10 female, were obtained from the conserved anatomical piece collection of the Anatomy Laboratory of the Federal University of Uberlândia. The preparation of the specimens consisted of fixation and dissection according to the routine procedures used in anatomical studies. After a detailed analysis of the specimens, it was verified that the lumbar plexus of Cebus apella is almost always separated in lumbar, sacral and coccygeal segments. There were considerable variations among the specimens and between the sides. The roots L2-L5 participated in the formation of the lumbar plexus, with higher frequency of L3 and L4, while the roots L4-S4. The right lumbar plexus was formed by L2, L3, and L4 (75.00% of cases), L3 and L4 (55.00%), L2, L3, L4 (20.00%), and L2, L3, L4 and L5 (5.00%), while on the left side there was participation of L2, L3, and L4 (80.00%), being that L3 and L4 (50.00%) and L2, L3, L4 and L5 (30.00%), and L5 is present in 15.00% and L2 and L3 in 5.00%. The number of anastomoses is variable.